A survey on occupational mental health at a private college in northern region of Peninsular Malaysia / Siti Farhana Hasanudin … [et al.] - Hasanudin, Siti Farhana; Mohd Safar, Fauziah; Saaidun, Noor Saidatul Natrah; Nik Abdullah, Nik Azlina (Universiti Teknologi MARA (UiTM), 2022)
Occupational mental health is one of the work-related stresses that hinder the employees optimal job performance and damages organizational effectiveness. Employees with mental health issue could suffer exhaustion, poor social interactions, having difficulties to complete/cope with everyday commands, weak memory, inability to concentrate, sleeping problems and unstable emotions. This will lead to employees' turnover, higher absenteeism, lower job productivity, performance, and satisfaction. As a result of absenteeism and turnover due to the mental health conditions, the company has to pay for direct costs (costs of care), indirect costs (productivity loss) and non-financial costs (costs of emotional and social health). Therefore, this study is conducted to investigate the relationship between job demand, interpersonal conflict, and COVID-19 pandemic on occupational mental health among employees at one of the private colleges in northern region of peninsular Malaysia. An online survey was performed among 171 employees working the college and Statistical Package for Social Science (SPSS) version 26.0 was utilized to generate the results to answer the research objectives. The statistical results confirmed that job demand, interpersonal conflicts and COVID-19 pandemic lead to occupational mental health. The findings are useful not only for the employees but also for the organization to improve the working conditions by considering the factors in this study.